Manajemen Perawatan Hipertensi Berbasis Pemberdayaan Masyarakat untuk Pencegahan Komplikasi di Kelurahan Agrowisata - Guna, Stephanie Dwi; Zulfitri, Reni; Misrawati, Misrawati; Arneliwati, Arneliwati; Aziz, Ari Rahmat (Unri Conference Series: Community Engagement, 2024)
Hypertension is a serious health issue that can lead to various complications, yet it is often poorly managed. This community service activity aims to enhance self-management among hypertension sufferers in Agrowisata Village, Rumbai District, Pekanbaru City. The methods employed in this initiative include blood pressure identification, free medication provision, family education regarding hypertension care, and the establishment of hypertension awareness cadres. Measurement results indicate that only 20% of patients have controlled blood pressure, with 75% not regularly taking antihypertensive medication. Education was provided to improve understanding of the importance of regular medication adherence, while the trained cadres are expected to support the sustainability of this program. Through these efforts, it is hoped that the community will be able to manage hypertension independently and prevent serious complications in the future.